Dogonić zrównoważony rozwój. Studenci SGGW o zmianach w domowej ekonomii = Catching up with sustainable development. Students of Warsaw University of Life Sciences (SGGW) on changes in home economics - Wachowiak, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Home economics and the way it functions is now a priority area in the daily lives of all people running households. Negative behaviors in these households, not only of a nutritional nature, have had an impact on global issues. Is being eco-friendly today a necessity or rather an individual preference? What optics define (and do they define) the changes in homeeconomics? How is this happening and in what direction? These issues were the topics of essays developed by first-year sociology students at the Warsaw University of Life Sciences (SGGW) in 2021. They were preceded by the presentation of the International Federation for Home Economics (IFHE), which has been at the vanguard of change in the field of home economics for over 100 years of its existence.
Keywords: domowa ekonomia; zrównoważony rozwój; ekologia; konsumeryzm; gospodarstwo domowe; dekonsumpcja; home economics; sustainable development; ecology; consumerism; household; deconsumption